Eleganca resnosti branja mladinske književnosti - Saksida, Igor (Jezik in slovstvo, 2014)
The contribution is focused on the method of interpretation of youth literature as demonstrated by the expert texts of Helga Glušič. The point of departure is the fundamental autopoetics emphasising the quality and the reader universality of this literary genre. Both starting points for interpretation and assessment can be identified in the author's interpretations of youth literature, particularly in A Hundred Slovenian Narrative Writers, in which two models of reading youth literature are intertwined: the interpretation of young readers' texts as an important part of an author's opus, and the focus on these texts in the case that an author has been marked in literary history as a youth writer.
Keywords: Glušič, Helga, 1934-2014; besedila; interpretacija besedil; otroška in mladinska književnost